The Effects of Physical and Transition Climate Risk on Stock Markets: Some Multi-Country Evidence - Marina Albanese; Guglielmo Maria Caporale; Ida Colella; Nicola Spagnolo (CESifo GmbH, 2024)
This paper examines the impact of transition and physical climate risk on stock markets using, for the first time in this context, the annual CCPI index calculated by Germanwatch as well as its components (in addition to a wide range of other indices) for 48 countries from 2007 to 2023. Specifically, a balanced panel VAR model is estimated to obtain impulse responses for the whole set of countries considered as well as for a subset including the EU-28 only; other methods such as Forecast Error Variance Decomposition and Local Projections (Jorda, 2005, 2022) are then applied for robustness checks. The results suggest a positive impact of transition risk on stock returns and a negative one of physical risk, especially in the short term. Further, while physical risk appears to have an immediate impact, transition risk is shown to affect stock markets also over a longer time horizon. Finally, national climate policies seem to be more effective when implemented within a supranational framework as in the case of the EU-28.
Keywords: C33; G12; G18; 330; climate change; physical risk; transition risk; stock markets; balanced panel VAR; impulse response analysis; local projections